Magnetic Plasmon Sensing in Twisted Split-Ring Resonators. (30th May 2012) - Cao, J. X.; Liu, H.; Wang, S. M.; Zheng, Y. J.; Zhu, C.; Wang, Y.; Zhu, S. N.
Abstract : We studied the sensing properties of stereo-SRRs metamaterials composed from two twisted split-ring resonators (SRRs). Due to the strong hybridization effect in the system, the polarization state of the transmitted wave is greatly changed at resonances. Since the stereo-SRRs structure is strongly coupled to the surrounding medium, the polarization change of the transmitted waves is quite sensitive to the refractive index change of the environment medium. The polarization ratio PR tran = T y /T x is used as sensing parameter and its figure of merit can reach 22.3 at the hybridized magnetic plasmon resonance. The results showed that the stereo-SRRs metamaterial can be applied to optical sensors an or other related field.